Watfa, Ägypten: Die Wasserversorgung ausgewählter Dörfer des Fayum in griechisch-römischer Zeit - Römer, Cornelia (e-Forschungsberichte des DAI, 2023)
Excavations in November 2012 at the site of Watfa, ancient Philoteris in the north-western Fayum focussed on features along the ancient canals. Two areas of possible harbours were investigated. Drillings were carried out in the canals to understand their depth and width. Of special interest is a well which is connected by an underground tunnel to the larger water reservoirs in the north of the village. The well was situated on a piece of land of minor dimensions close to the village; it may have been used as an orchard or vineyard. Already in the pharaonic period, wells were typically part of vineyards because these required sophisticated irrigation systems.